2017
DOI: 10.1038/ncb3573
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific CTCF–cohesin-mediated chromatin architecture delimits enhancer interactions and function in vivo

Abstract: The genome is organised via CTCF/Cohesin binding sites, which partition chromosomes into 1-5Mb topologically associated domains (TADs), and further into smaller sub-domains (sub-TADs). Here we examined in vivo an ~80kb sub-TAD, containing the mouse α-globin gene cluster, lying within a ~1Mb TAD. We find that the sub-TAD is flanked by predominantly convergent CTCF/cohesin sites which are ubiquitously bound by CTCF but only interact during erythropoiesis, defining a self-interacting erythroid compartment. Wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
250
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(280 citation statements)
references
References 54 publications
16
250
1
Order By: Relevance
“…Single-molecule mRNA FISH confirmed these findings by demonstrating that, at the single-cell level, the expression of these two genes becomes increasingly correlated with either deletion of the intervening CTCF/BRD2 cooccupied site or with BRD2 depletion. Conceptually analogous findings were recently reported at another erythroid gene locus, in which mutation of CTCF sites at the α-globin gene cluster in mice resulted in the formation of new contacts between the α-globin enhancer and the promoters of adjacent genes normally protected from its influence (Hanssen et al 2017).…”
Section: Bets As Insulator/architectural Proteinsmentioning
confidence: 53%
“…Single-molecule mRNA FISH confirmed these findings by demonstrating that, at the single-cell level, the expression of these two genes becomes increasingly correlated with either deletion of the intervening CTCF/BRD2 cooccupied site or with BRD2 depletion. Conceptually analogous findings were recently reported at another erythroid gene locus, in which mutation of CTCF sites at the α-globin gene cluster in mice resulted in the formation of new contacts between the α-globin enhancer and the promoters of adjacent genes normally protected from its influence (Hanssen et al 2017).…”
Section: Bets As Insulator/architectural Proteinsmentioning
confidence: 53%
“…Interestingly, AMIGO2 and its SEs are located within the same putative topologically associating domain (TAD) (Dekker and Heard, 2015) and lamina-associated domain (Fu et al, 2015), as suggested by flanking H3K27me3, macroH2A1, and macroH2A2 repressive domains, respectively, as well as CTCF occupancy (Hanssen et al, 2017) (Figure 6A). This region also contains PCED1B , which is not expressed (Table S1) and therefore unlikely to be regulated by these SEs.…”
Section: Resultsmentioning
confidence: 99%
“…We focused our analysis on a ~3.3 Mb region containing the well-characterized a-globin genes and their associated regulatory elements. The a-globin genes are regulated by five erythroidspecific enhancer elements (R1-R4 and Rm), which classify as a super-enhancer 20 , and interact with the gene promoters within a TAD flanked by multiple CTCF-binding elements [21][22][23][24] (Supplementary Figure 2). We generated a single-cell RNA-seq dataset 25 , which is the first scRNA-seq dataset to include the full course of in vivo erythroid differentiation through to terminal differentiation in the mouse (Supplementary Figure 5).…”
mentioning
confidence: 99%